A serological type II collagen neoepitope biomarker reflects cartilage breakdown in patients with osteoarthritis - Solveig Skovlund Groen; Dovile Sinkeviciute; Anne-Christine Bay-Jensen; Christian S. Thudium; Morten A. Karsdal; Simon Francis Thomsen; Sven Lindemann; Daniela Werkmann; Joseph Blair; Line Mærsk Staunstrup; Patrik Önnerfjord; Lars Arendt-Nielsen; et al. (Osteoarthritis and Cartilage Open, 2021)
Objectives: There is an unmet medical need for biomarkers in OA which can be applied in clinical drug development trials. The present study describes the development of a specific and robust assay measuring type II collagen degradation (T2CM) and discusses its potential as a noninvasive translational biomarker. Methods: A type II collagen specific neoepitope (T2CM) was identified by mass spectrometry and monoclonal antibodies were raised towards the epitope, employed in a chemiluminescence immunoassay. T2CM was assessed in bovine cartilage explants with or without MMP-13 inhibitor, and explant supernatants were analyzed by Western blot. T2CM was measured in plasma samples from one study (n ​= ​48 patients) where OA patients were referred to total knee replacement (TKR). Additionally, T2CM was quantified in serum from OA patients receiving salmon calcitonin treatment (sCT) (n ​= ​50) compared to placebo (n ​= ​57). Results: The T2CM assay was technically robust (13/4 ​% inter/intra-variation) and specific for the type II collagen fragment cleaved by MMP-1 and -13. The MMP-13 inhibitor reduced the T2CM release from bovine cartilage explants receiving catabolic treatment. These results were confirmed by Western blot. In human end-stage OA patients (scheduled for TKR), the T2CM levels were elevated compared to moderate OA (p<0.004). The OA patients receiving sCT had lower levels of T2CM compared to placebo group after 1, 6, and 24 months of treatment (p ​= ​0.0285, p ​= ​0.0484, p ​= ​0.0035). Conclusions: To our knowledge, T2CM is the first technically robust serological biomarker assay which has shown biological relevance in ex vivo models and OA cohorts. This suggests that T2CM may have potential as a translational biomarker for cartilage degradation.